Gastrodin Inhibits Store-Operated Ca2+ Entry and Alleviates Cardiac Hypertrophy - Zheng, Changbo; Lo, Chun-Yin; Meng, Zhaoyue; Li, Zhichao; Zhong, Mingkui; Zhang, Peng; Lu, Jun; Yang, Zhaoxiang; Yan, Fuman; Zhang, Yunting; Huang, Yu; Yao, Xiaoqiang (Frontiers in Pharmacology, 2017)
Cardiac hypertrophy is a major risk factor for heart failure, which are among the leading causes of human death. Gastrodin is a small molecule that has been used clinically to treat neurological and vascular diseases for many years without safety issues. In the present study, we examined protective effect of gastrodin against cardiac hypertrophy and explored the underlying mechanism. Phenylephrine and angiotensin II were used to induce cardiac hypertrophy in a mouse model and a cultured cardiomyocyte model. Gastrodin was found to alleviate the cardiac hypertrophy in both models. Mechanistically, gastrodin attenuated the store-operated Ca2+ entry (SOCE) by reducing the expression of STIM1 and Orai1, two key proteins in SOCE, in animal models as well as in cultured cardiomyocyte model. Furthermore, suppressing SOCE by RO2959, Orai1-siRNAs or STIM1-siRNAs markedly attenuated the phenylephrine-induced hypertrophy in cultured cardiomyocyte model. Together, these results showed that gastrodin inhibited cardiac hypertrophy and it also reduced the SOCE via its action on the expression of STIM1 and Orai1. Furthermore, suppression of SOCE could reduce the phenylephrine-induced cardiomyocyte hypertrophy, suggesting that SOCE-STIM1-Orai1 is located upstream of hypertrophy.